CNC Prototype: a new resource for maker environments as didactic support for teaching/learning in Educational Robotics courses (Research, Society and Development, 2022)
With the advancement of technology and the large volume of content on the web in recent decades, the use of CNC milling machines (Computer Numerical Control) in the industrial environment has increased, gaining considerable attention in the manufacture of parts. This article proposes the construction of an affordable, low-investment CNC prototype for the manufacture of PCBs (printed circuit boards) in order to instigate the academic strengthening of teaching and learning in educational robotics courses, contributing to new low-cost prototyping. As a result from the didactic point of view, it is based on an educational model to support the knowledge and maker experiences of new students, demonstrating that this technology can be disseminated to several schools, encouraging research and the development of new prototypes.